Revitalisasi Masyarakat Ekologis: Program Pengabdian Masyarakat melalui Aksi Sosial Reboisasi di Desa Nagrak Kabupaten Subang - Setiawan, Tomi; Alfarobi, John (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This paper aims to explain social action programs to encourage the revitalization of ecological communities that emphasize the ecological principles within a social framework to build a harmonious relationship between humans and their natural environment. In the Indonesian context, the real impacts of climate change, particularly forest destruction, have catalyzed various initiatives, including the Climate Village Program (ProKlim), which promotes community engagement in climate management. The methodology used in this program includes several stages, from preparatory activities and field analysis to implementation, involving collaboration between lecturers, students, and local communities. This social action was implemented in Nagrak Village in Ciater District, Subang Regency, as a study. The village faces challenges posed by climate change and environmental pressures stemming from tourism activities. To address these issues, social action was implemented in the form of a reforestation initiative, concentrating on planting 100 trees as a mitigation strategy and an effort to raise community awareness. The outcomes of this program go beyond restoring the ecological functions of the land; they also include increasing ecological literacy and empowering the community in addressing climate change. Tree planting is done with careful consideration of the needs of the local ecosystem, the adaptability of the tree species, and long-term sustainability. This program of activities concludes that ecological community revitalization initiatives through community-based collective action can serve as an effective model to mitigate climate change and foster more ecologically resilient communities.